SIFAT DAN PERILAKU BURUK MANUSIA SEBAGAI SUMBER INSPIRASI PENCIPTAAN KARYA SENI LUKIS - Hasan, H. (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2015)
Creation report compiled under the title "The nature and Bad Behavior Humans as a Source of Inspiration Creation of Art Works" is motivated by the problems associated with the bad behavior of human nature and the social life in this country and in the other hemisphere. The purpose of the report is the creation and deepen understanding of the theme and then visualized on the basic idea and created a metaphor in works of art related to the title is lifted. Methods used his creation stages include: pre-creation, creation and post-creation.After going through the pre-stage of creation, then moved to the stage of creation which explains some of the process include: design sketches and shapes composition, manufacture background, the removal of sketches and drafts composition forms on the canvas, coloring, details, improvisation, and finishing. In the creation of this post is a process gives fixatif works made in order to become more maximal and durable.The creation of the work will run smoothly with maximum results when there is a unified whole or mutual support between the selection of appropriate materials and work on good engineering capability in the process of creating the work that has been programmed, so the results are as expected.Keywords: bad behavior, human, creation of works, painting